Periadrenal inflammatory myofibroblastic tumour: half a decade before cure. Issue 2 (1st February 2019) - Abdul Ghani, Rohana; Mohamed Shah, Fatimah Zaherah; Hanafiah, Mohammad; Abdul Aziz, Mardiana
Abstract : A 30-year-old ex-smoker with a background history of childhood asthma presented with worsening shortness of breath despite receiving high doses of oral corticosteroid for pemphigus vulgaris which was diagnosed 5 years earlier. A high-resolution CT examination of the thorax reported non-specific bronchiectatic changes and revealed an incidental suprarenal mass. A subsequent CT scan confirmed a large adrenal mass with areas of necrosis and calcification. Serum renin and aldosterone, urinary catecholamine and 5-hydroxyindoleacetic acid were within normal limits. Surgical intervention was delayed due to difficulty in optimising preoperative respiratory functions. He finally underwent a midline laparotomy for removal of the tumour. Histopathological examinations revealed extrapulmonary inflammatory myofibroblastic tumour arising from the periadrenal soft-tissue, with presence of normal adrenal gland. He showed immediate improvements of his asthmatic symptoms and pemphigus vulgaris following the surgery. His oral steroid was rapidly reduced and he achieved complete remission 2 months later.